Acetabular Defect Reconstruction with Trabecular Metal Augments: Study with Minimum One-year Follow-up - Dwivedi, Chirayu (Hip Pelvis, 2017)
PURPOSE: High rates of mechanical failure have been reported in type III acetabular defects. Recently porous trabecular metal augments have been introduced with, excellent biomechanical characteristics and biocompatibility, allowing early stability and greater bone ingrowth. The aim of the study was to assess the short term clinical and radiological outcome of the trabecular metal augments. MATERIALS AND METHODS: We performed, 22 revision total hip arthroplasties (THA) and 6 primary THA (total 28) using trabecular metal augments to reconstruct acetabular defect between 2011 to 2015. Among 28 patients, 18 were males, 10 females. Mean age of patients was 61.21 years. Paprosky classification for acetabular bone defects was used. Eighteen cases were classified as grade 3 A and 10 cases as grade 3B. Hip center was calculated in each case preoperatively and compared postoperatively to check whether it has been brought down. Clinical outcome assessed using Harris hip score (HHS) and radiological outcomes as osteolysis in acetabular zones and osseointegration, according to Moore's criteria. RESULTS: HHS improved from 58.00 to 86.20. Centre of rotation of hip joint corrected from 38.90 mm preoperatively to 23.85 mm postoperatively above the interteardrop line. Among 28 patients, 18 patients had three or more signs of osseointegration (Moore's criteria), during final follow up and 10 had one/two signs. No radiolucency, osteolysis, or loosening found during follow up radiographic examination. CONCLUSION: Our study showed that trabecular metal augments were highly satisfactory in short term. However, long term study is required for better evaluation.